Implementation study reporting diagnostic accuracy, outcomes and costs in a multicentre randomised controlled trial of non‐expert lung ultrasound to detect pulmonary oedema. (17th June 2019) - Baker, Kylie; Brierley, Stephen; Kinnear, Frances; Isoardi, Katherine; Livesay, Georgia; Stieler, Geoffrey; Mitchell, Geoffrey
Abstract: Background: Lung ultrasound experts claim that 'B line' artefacts herald pulmonary oedema, but links between early recognition and improved outcome are unconfirmed, particularly for non‐expert clinicians. Objective: Assess individual and system impacts of early, non‐expert lung ultrasound (LUS) in breathless older patients. Methods: Prospective single‐blinded randomised controlled trial of point of care LUS by non‐expert clinicians, augmenting ED assessment of patients over 60 years, presenting with dyspnoea. After brief training, clinicians at three hospitals used computer‐generated block randomisation envelopes to allocate a convenience sample of consenting presenters to conventional or LUS‐augmented management. ED provisional diagnosis was compared to a post‐discharge chart audit diagnosis, blinded to ultrasound findings. Secondary outcomes were the length of stay in ED and hospital, costs and discharge destinations. Results: From three sites, 224 controls were compared with 218 interventions. LUS improved diagnostic accuracy, with a small effect size in favour of LUS (risk difference: 6.5%, 95% CI 0.9–12) and a number needed to scan of 16 (95% CI 8–107). With LUS, ED and hospital stay increased non‐significantly, while discharge destination trends improved. No harm ensued. Conclusions: Non‐expert LUS augmenting dyspnoea workup may improve diagnostic accuracy, but did not significantly alter costs or outcomes in the ED or the hospital. Trial registration: Australia and New Zealand Clinical Trials Registry (ACTRN12613001023741).